Deoxyribozymes: New Therapeutics to Treat Central Nervous System Disorders - Grimpe, Barbara (Frontiers in Molecular Neuroscience, 2011)
This mini-review focuses on a knockdown technology called deoxyribozymes, which has rarely been utilized in the field of neurobiology/neuroscience. Deoxyribozymes are catalytic DNA molecules, which are also entitled DNA enzyme or DNAzyme. This mini-review presents a description of their development, structure, function and therapeutic application. In addition, information on siRNA, ribozymes and antisense are given. Further information on two deoxyribozymes against c-Jun and xylosyltransferase (XT) mRNA are summarized of which the first is important to influence many neurological disorders and the last potentially treats spinal cord injuries (SCIs). In particular, insults to the central nervous system (CNS) such as SCI generate an inhibitory environment (lesion scar) at the injury site that prevents the endogenous and therapy-induced axonal regeneration and thereby limits repair strategies. Presently, there are no treatments available. Hence, deoxyribozymes provide an opportunity for new therapeutics that alter the inhibitory nature of the lesion scar and thus promote axonal growth in the injured spinal cord. When used cautiously and within the limits of its ability the deoxyribozyme technology holds promise to become a major contributing factor in repair strategies of the CNS.